GLP−1 receptor agonists for the treatment of obesity: Role as a promising approach - Wang, Jing-Yue; Wang, Quan-Wei; Yang, Xin-Yu; Yang, Wei; Li, Dong-Rui; Jin, Jing-Yu; Zhang, Hui-Cong; Zhang, Xian-Feng (Frontiers in Endocrinology, 2023)
Obesity is a complex disease characterized by excessive fat accumulation which is caused by genetic, environmental and other factors. In recent years, there has been an increase in the morbidity, disability rate,and mortality due to obesity, making it great threat to people’s health and lives, and increasing public health care expenses. Evidence from previous studies show that weight loss can significantly reduce the risk of obesity-related complications and chronic diseases. Diet control, moderate exercise, behavior modification programs, bariatric surgery and prescription drug treatment are the major interventions used to help people lose weight. Among them, anti-obesity drugs have high compliance rates and cause noticeable short-term effects in reducing obese levels. However, given the safety or effectiveness concerns of anti-obesity drugs, many of the currently used drugs have limited clinical use. Glucagon-like peptide-1 receptor (GLP-1R) agonists are a group of drugs that targets incretin hormone action, and its receptors are widely distributed in nerves, islets, heart, lung, skin, and other organs. Several animal experiments and clinical trials have demonstrated that GLP-1R agonists are more effective in treating or preventing obesity. Therefore, GLP-1R agonists are promising agents for the treatment of obese individuals. This review describes evidence from previous research on the effects of GLP-1R agonists on obesity. We anticipate that this review will generate data that will help biomedical researchers or clinical workers develop obesity treatments based on GLP-1R agonists.